The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/acs.inorgchem.0c03529
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Achieving Long-Wavelength Near-Infrared Luminescence of Diimineplatinum(II) Complexes

Abstract: Although many strategies have been used to help design effective near-infrared (NIR) luminescent materials, it is still a huge challenge to realize long-wavelength NIR luminescence of diimineplatinum(II) complexes in the solid state. Herein, we have successfully achieved long-wavelength NIR luminescence of a family of diimineplatinum(II) complexes based on a new strategy that combines a one-dimensional (1D) "Pt wire" structure with the electronic effect of the substituent. The structures of six solvated diimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In 2021, Ni et al reported a series of diimine Pt(II) complexes by combining the one-dimensional (1D) ''Pt wire'' structure with the electronic effects of substituents. 121 The electron-withdrawing group in the pyridine ligand and the electron-donating group in the phenylacetylene ligand can greatly reduce the HOMO-LUMO energy gap. In the solid state, these complexes showed low-energy absorption bands between 600 and 783 nm due to the MMLCT transition.…”
Section: Nir-i Mmcsmentioning
confidence: 99%
“…In 2021, Ni et al reported a series of diimine Pt(II) complexes by combining the one-dimensional (1D) ''Pt wire'' structure with the electronic effects of substituents. 121 The electron-withdrawing group in the pyridine ligand and the electron-donating group in the phenylacetylene ligand can greatly reduce the HOMO-LUMO energy gap. In the solid state, these complexes showed low-energy absorption bands between 600 and 783 nm due to the MMLCT transition.…”
Section: Nir-i Mmcsmentioning
confidence: 99%
“…Electronic absorption spectra of the Pt(II) complexes in solution exhibit wide nonstructured bands in the 330–443 nm range (Table and Figure a,d). The spectra generally correspond to a superposition of the diimine-based ππ* transitions, acetylene-based intraligand charge transfer (ILCT), and metal-to-ligand charge transfer (MLCT) bands. ,,, The intense nonstructured acetylene-based CT transition bands dominate in most spectra; however, the spectra of cyclometalated complexes 7 – 10 exhibit lower contributions of these transitions and relatively high energy absorption corresponding to the {Pt(C ∧ N ∧ N)} fragment.…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests the existence of the weakest Pt···Pt stacking interaction for Pt­(II) complex 3 in a neat thin film, probably attributed to a combination of both electronic and steric effects among these fluoroalkyl substituents. It is also notable that, although there are a number of Pt­(II) complexes capable of showing efficient saturated red and even NIR emission in the solid state or as crystalline materials, this class of azolate Pt­(II) complexes represent one rare example, where the well-stacked structure in a thin film was easily assembled by the chemical vapor deposition (or thermal vacuum deposition) technique.…”
Section: Resultsmentioning
confidence: 99%